Calculation of Hydrogen Bonding Enthalpy Using the Two-Parameter Abraham Equation - Boris N. Solomonov; Mansur B. Khisamiev; Mikhail I. Yagofarov (Liquids)
In this work, an approach to the calculation of hydrogen bonding enthalpies is proposed. It employs the correlation proposed by M.H. Abraham, establishing the connection between the equilibrium constant (KHB) and acidity (<semantics><msubsup>α2H</msubsup></semantics>) and basicity (<semantics><msubsup>β2H</msubsup></semantics>) parameters: log KHB = 7.354 · <semantics><msubsup>α2H</msubsup></semantics> · <semantics><msubsup>β2H</msubsup></semantics> − 1.099. Hydrogen bonding enthalpy (ΔHBH) is found using the compensation relationship with Gibbs energy (ΔHBG): ΔHBG = 0.66 · ΔHBH + 2.5 kJ·mol−1. This relationship enables the calculation of the enthalpy, Gibbs energy and entropy of hydrogen bonding. The validity of this approach was tested against 122 experimental hydrogen bonding enthalpies values available from the literature. The root mean square deviation and average deviation equaled 1.6 kJ·mol−1 and 0.5 kJ·mol−1, respectively.